Solve: x^2-7x+6=0

Factorise the equation and then equate each set of brackets to 0 to obtain both possible solutions. 

By factorising: (x-6)(x-1)=0 

Therefore: x=6 or x=1

Answered by Phoebe G. Maths tutor

5379 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

What is the equation of the tangent to the circle (x-5)^2+(y-3)^2=9 at the points of intersection of the circle with the line 2x-y-1=0


How do i find dy/dx in terms of t for two parametric equations that are in terms of t.


What is product rule differentiation?


A geometric progression has first term 3 and second term -6. State the value of the common ratio.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences